STRATEGI KOMUNIKASI PUBLIK DALAM MENINGKATKAN CITRA SEKOLAH - Fathor Rosi; Agus Nu’man; Sandiko Sandiko; Fathor Rozi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2022)
This study examines public communication strategies to improve the school's image so that people believe and are interested in sending their children to the institution. This study uses a descriptive qualitative approach. The type of research is a case study with the research location being at SMP Nurul Huda Peleyan Kapongan Situbondo. Data collection techniques were carried out by observation and in-depth interviews and then analyzed through the stages of data reduction, data presentation, and data verification. The results of the research obtained are that the implementation of public communication at SMP Nurul Huda Peleyan Kapongan Situbondo is carried out by preparing a layered strategy which is then realized by conducting internal and external communication (publication to the wider community through print media and social media). The implication is that the public relations of educational institutions must establish communication and cooperation with internal and external parties so that school publications can be realized optimally.